METODE DAKWAH DALAM MENGOPTIMALISASI KESADARAN BERAGAMA MANUSIA USIA LANJUT - Nurwahida Alimuddin (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2015)
This paper deals with how is Islamic preaching conducted to optimize the elderly's religious consciousness at the nursing home Ar-Rahman, Kamonji, subdistrict of Palu Barat. This research used a qualitative-descriptive method with a sociological ad psychological approach. The findings show that the nursing home Ar-Rahman runs well. And the da'wah activity in this home is classified into two verbal and non- verbal preaching. Optimization of religious awareness for the elderlies is through strengthening the cooperation with Palu's local government and giving a professional guidance continously. As a local government's partner, financial support from the government and alms from society are necessary to optimize the infrastructures to support the activity of promoting religious awareness among the elderlies at this nursing home. However, in this process of optimization, it is not exhaustive enough because there is no systematic guidance which directs da'wah activity in optimizing religious awareness among the elderlies.